An Analysis Of Cross Capacity Development Planning Based On The Replacement Mechanical Signals To Electrical Signals At Merapi Station - Suryono, Totok; Nurrachman, Fadhlan; Kurniawan, Agil Krisna; Septianti, Ainun (Jurnal Teknik Transportasi, 2025)
PT. Kereta Api Indonesia (Persero) from 2021 is carrying out development planning in the Regional Division III (DIVRE III) South Sumatra to meet the increasing coal transportation projections. This development is carried out to support national logistics distribution with the main commodity coal towards 105 million tons / year. In this study using quantitative descriptive methods, researchers will discuss the analysis of capacity development planning based on the replacement of mechanical signals into electrical signals at the Merapi station using 4 analyses, namely: Analysis of transportation projections, analysis of headway and cross capacity, analysis of plan design, technical economic analysis. Based on the results of the researcher's observation and data collection, the researcher can analyze and conduct a discussion based on the analysis that has been determined. Based on the calculation analysis, it was found that the value of 126% (126 percent) increased coal transportation projections from 2022 – 2032 (10 years). Increased capacity of the Banjarsari – Merapi road plot and the Merapi – Sukacinta road plot, as well as the relationship between the train program that has been prepared in 2021-2026. In the design of the plan, there are several signaling aspects that are added and relocated for these needs and the profit from a coal transportation amounting to Rp.12,491,832,236,400 in 2027-2032, in the sense that it can be profitable in the business aspect